Hepatitis B in Moroccan blood donors: a decade trend of the HBsAg prevalence in a resources limited country. Issue 6 (10th July 2013) - Adouani, B.; Alami, R.; Laouina, A.; Benahadi, A.; Boulahdid, S.; Mokhtari, A.; Soulaymani, A.; Abouyoub, A.; Benajiba, M.
SUMMARY Objectives To calculate the hepatitis B surface antigen (HBsAg) reactive rate for 2011 blood donors (BD) across Morocco. In addition, to monitor the profile of donors bearing the HBsAg during 2000 and 2011, we calculated the percentage of the prevalence in both sexes, in different age groups and in first‐time replacement and regular BD from the Rabat Regional Blood Transfusion Centre. Background Hepatitis B is a viral infection that spreads through blood and other biological fluids. The hepatitis B virus remains one of the most common serious complications of transfusion. No information exists on the real prevalence of hepatitis B in Moroccan BD. Methods For the 2011 national HBsAg reactive rate, the percentage was calculated based on enzyme‐linked immunosorbent assay (ELISA) results of the 232 190 blood donations collected around the country. For the Rabat blood Centre, we calculated the hepatitis B sero‐prevalence from donations made at the donors' suite during 2000 and 2011. Results The national prevalence of HBsAg was 1·34%. The HBsAg variations among different regions was between 0·43 and 2·86%. The Rabat donors' suite hepatitis B prevalence decreased from 2·47% in 2000 to 0·91% in 2011 (P < 0·001). In both years, family/replacement donors were found as safe as first‐time BD and female donors were the safest. Conclusions These results, presented for the first time in the country, mapped the hepatitis B distribution across Morocco in a healthy population. The findings of this study could be of great importance in setting up strategies for the recruitment of the BD and keeping blood safety at the highest level.